FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE ENGINEERS ON THE BASIS OF INTERDISCIPLINARY INTEGRATED EDUCATION OF PHYSICS - Beknozarova Zamira Farmanovna (American Journals Publishing, 2023)
In the article, the professional competence of engineering students in physics based on interdisciplinary integrated education the method of formation is explained.
Keywords: engineer, competence, competence, irrigation, hydraulic engineering, integration.